Determination of metals contamination in rock melon (cucumis melo) and coco peat / Nur Firdaus Abdul Rashid and Adzmi Yaacob - Abdul Rashid, Nur Firdaus; Yaacob, Adzmi (Universiti Teknologi MARA, Perlis, 2015)
Fresh fruit is one of the sources of these trace metals which can be obtained easily with reasonable price. Trace metals content when exceed certain concentration can however contribute to harmful effect to human. This study analyzes the concentration of selected metals that include Aluminum (Al), Boron (B), Cobalt (Co), Chromium (Cr), Copper (Cu), Iron (Fe), Manganese (Mn), Nickel (Ni), Lead (Pb) and Zinc (Zn) in rock melon (Cucumis melo) randomly selected from 5 different locations as well as in the coco peat used as growth media for the crop. The results were compared with the maximum allowable limits (MAL) set by Malaysian Food Act (1983), Malaysian Food Regulation (1985) and Federal Food Drug Administration (FFDA) 1997. The finding from the study showed that there are six elements were found to be exceed the maximum allowable limits (MAL) in Cucumis melo. They are Al, Cr, Cu, Fe, Pb and Zn, 60.14±0.393 ppm, 6.42 ±0.170 ppm, 17.4 ± 0.079 ppm, 102.62 ± 0.114 ppm, 1.82 ± 0.235 ppm and 11.97± 0.821 ppm respectively. B, Mn and Ni were not exceeding the MAL. However, Co barely detectable by ICP (OES). Heavy metals content in Cucumis melo should be of great concern because of its popularity in Malaysia (The Star, 2013). In addition, heavy metals are toxic to human and usually accumulate in organs such as kidney, liver and heart. This study indicates that there are six elements of metals in rock melon and coco peat exceed the MAL.